Automatización del proceso de pasteurización de leche en la fábrica de helados iglú del cantón Pujilí provincia de Cotopaxi - Caisabanda Toapanta, Marco Alexander (2022)
In the Iglú ice cream factory, it was identified that there is no automatic system in the milk pasteurization process, which leads to excessive time for the operator so the objective of this technological proposal is to implement an automatic system using existing technologies in the market, the methodology consists of three levels which are: field equipment, which includes the MLX90614 temperature sensor, the HW 103 level sensors, and the machine's actuators, such as the solenoid valves for the water inlet and outlet system, and an agitator for uniform mixing of the raw material. The control equipment includes a Mitsubishi PLC programmable logic controller FX3U-24MR series, which generates the conditions and restrictions for actuators and pre-actuators activation, performs the acquisition and processing of variables measured by the sensors, and executes the actions indicated, another main function of this PLC is the exchange of information with the monitoring system through RS-232 serial communication via DB9 port. In the operation and supervision equipment, a Kinco GL070E series touch screen was used, which through its HMI system allows real-time monitoring. The implementation of the automatic system facilitates the operator's work with a time reduction of 0.3 HOURS equivalent to 18 MINUTES, having a reduction scale of 19.41% of what it normally took in the process inside the Iglú ice cream factory.